Mental Health Strategies Informed by Black Feminist Thought - Oliphant Vanessa Nicole; Broyles Deja; Clement Déjà N.; Wingate LaRicka R. (Open Cultural Studies, 2022)
There is currently a gap in the literature that explicitly connects Black feminist thought with psychological theory, research, or intervention. This article review aims to assist in filling the gap and inspire scholars to actively utilize the knowledge of Black feminism and apply it to culturally specific mental health resources for Black women. There is a need for a new generation of Black feminists to intentionally center Black women’s mental health in psychological research and therapeutic practices. Black women’s mental health is an important part of Black feminism, and accordingly psychological theory, research, and intervention should actively incorporate Black feminist thought. This article seeks to call attention to specific ways Black women can preserve and strengthen their mental health and maintain resiliency. Specifically, this review highlights three Black feminist-informed strategies that can aid in supporting Black women’s mental health: practicing essential/critical affirmations, raising Black consciousness, and intentional self-definition.